EXtract of oil palm empty fruit bunches waste as an potential insecticide for controlling Spodoptera frugiperda J. E. SMITH - Nurhajijah; Widihastuty; Wahyuni Umami Harahap; Wizni Fadhillah; Imam Hartono Bangun; Sasmita Siregar (Penerbit Universiti Kebangsaan Malaysia, 2024)
The percentage of attacks by Spodoptera frugiperda in Indonesia has reached 94% and is still increasing due to the use of chemical pesticides, which might have led some S. frugiperda to develop resistance. This problem must be addressed immediately in order to prevent continued losses for farmers. Moreover, an alternative method to control pests is by using natural materials that can potentially serve as insecticide, namely the liquid smoke of the empty oil palm fruit bunches (OPEFB). In this study, there were four treatments and four replications were conducted. The treatment was carried out in the field and in the laboratory. The treatments for the application of liquid smoke as vegetable pesticide in the laboratory were J1: control, J2: 10.0 ml/l, J3: 15.0 ml/l, and J4: 20.0 ml/l. Meanwhile, the treatments for the application of liquid smoke as vegetable pesticide in the field used a non-factorial randomized block design with the following treatments: H1: farmer application, H2: 10.0 ml/l, H3: 15.0 ml/l, and H4: 20.0 ml/l. The results showed that the J2, J3, and J4 treatments carried out in the laboratory had the highest proportion of mortality, with an average mortality percentage of 100% on day 6. Meanwhile, the intensity of S. frugiperda attacks indicated the highest attack on H1, which was the treatment carried out by farmers, with a value of 32.0% damage. In addition, the lowest attack by S. frugiperda was observed in the H4 treatment, which was 11%. This study provides important data to aid in the understanding of the secondary compounds contained in OPEFB liquid smoke and recommended concentrations in the application of liquid smoke against S. frugiperda on maize plant